The Independence of Journalism in Medan: Challenges and Realities in Performing Journalistic Duties - Taufik Wal Hidayat; Ilma Saakinah Tamsil; Selamat Riadi; Khairullah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Working as a journalist has a routine that is basically a need for information that the public wants. The routine that is carried out does not recognize any time and conditions, in other words, it must always be standby / ready to do coverage. However, most people think that the job of a journalist looks relaxed and easy-going because it is not bound by a schedule like most people in the office. But actually, the work of journalists is very demanding and risky. The work of journalists every day, regardless of time, place and conditions, is directly related to the nine principles of journalism, one of which is the fourth principle which states that journalists must maintain independence in their journalistic duties. The purpose of this study is to analyze the independence of journalists in carrying out their journalistic duties in Medan City. This research uses descriptive method with qualitative approach. The research was conducted in Medan City for 5 months using data collection techniques namely observation, interviews, and documentation. The conclusion of the research related to the application of journalists' independence in carrying out journalistic duties in Medan City is that it cannot be fully realized, due to many conflicts of interest.